Boolean Quiz(BeeQ) / Muhammad Naif Ihsan Shuhaimi, Ahmad Zaki Aiman Abdul Rashid and Ahmad Faiz Mohd Radzi - Shuhaimi, Muhammad Naif Ihsan; Abdul Rashid, Ahmad Zaki Aiman; Mohd Radzi, Ahmad Faiz (2015)
Boolean quiz(BeeQ) is a quiz game based on logic gates input where many switch is used to indicate the input for the quiz e.g 1 or 0 this occurs when the user key in the input by toggling the switch. User can key in 10 input which is a combination of binary numbers to achieve the output which is a waving hand. The waving hand is operated using servo motor and it will operate once the binary or inputs that has been keyed in is correct. Therefore, this project can be concluded that the input for this project is by toggling the switch (1 or 0) and the output is the waving hand and LED. This project consist of different types of logic gates such as OR, AND, NOT, NOR, NAND and X-OR. Most people knew that the output coming from each of these logic gates produces different output. The user of this project must come up with at least a paper to draw the schematic diagram first and to determine its output. Anyone can guess the answer but any theoretical answer needs explanation therefore calculating it first is a must for this project.